2021
DOI: 10.1111/adj.12828
|View full text |Cite
|
Sign up to set email alerts
|

Use of dental services among middle‐aged adults: predisposing, enabling and need variables

Abstract: Objectives To examine if making a visit, number of visits and services varied by predisposing (gender, perceived health competence, education, previous relief of pain visit), enabling (dental anxiety, income, social support) and need (perceived need, number of teeth and oral pain) characteristics. Methods Dental visiting and services data from a sample of middle‐aged South Australian adults were collected from 61% of participants at 12‐months (n = 603) and 59% after 24‐months (n = 583). Visiting over 2‐years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The relationship between DFA and dental attendance was examined in 57 articles ( n = 15 pediatric, n = 42 adult). The avoidance of or infrequent dental visits were linked with higher levels of DFA in children and adolescents [ 3 , 7 , 45 , 50 , 110 , 121 , 148 , 155 , 156 , 157 , 158 , 159 ] as well as adults [ 4 , 8 , 21 , 39 , 40 , 54 , 57 , 61 , 62 , 63 , 65 , 66 , 101 , 102 , 125 , 126 , 129 , 131 , 133 , 135 , 136 , 138 , 140 , 142 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Sporadic dental attendance as a child, compared to regular attendance, was associated with incre...…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between DFA and dental attendance was examined in 57 articles ( n = 15 pediatric, n = 42 adult). The avoidance of or infrequent dental visits were linked with higher levels of DFA in children and adolescents [ 3 , 7 , 45 , 50 , 110 , 121 , 148 , 155 , 156 , 157 , 158 , 159 ] as well as adults [ 4 , 8 , 21 , 39 , 40 , 54 , 57 , 61 , 62 , 63 , 65 , 66 , 101 , 102 , 125 , 126 , 129 , 131 , 133 , 135 , 136 , 138 , 140 , 142 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Sporadic dental attendance as a child, compared to regular attendance, was associated with incre...…”
Section: Resultsmentioning
confidence: 99%
“…Previous research that has used the Andersen model to assess socioeconomic disparities in the utilization of dental services has shown that enabling factors are key predictors [30]. Significant socioeconomic predictors included income [31][32][33][34][35][36][37], education [32,33,[35][36][37][38][39][40][41][42], wealth [32,41], dental health insurance coverage [32,35,40,43,44], and social support [28,34,43]. One study in Saudi Arabia used the Andersen model to investigate the utilization of dental services but only among children [45].…”
Section: Using the Andersen Healthcare Utilization Model As A Theoret...mentioning
confidence: 99%
“…A deeper understanding of the different barriers affecting access to and use of dental services is necessary to achieve this (4). The affordability of dental treatments has been largely recognized as one of the leading reasons why many adults delay or avoid the use of dental services (5,6). Although research suggests that affordability is a substantial barrier to using dental services, there is little evidence of progress toward ensuring that dental services are affordable (6).…”
Section: Introductionmentioning
confidence: 99%